Polypropylene composition with low linear expansion, high rigidity and high heat resistance and preparation method thereof
By introducing high aspect ratio whiskers and fluorogen mica into the polypropylene material and using lateral feeding and reverse shear module processes, the problems of high linear expansion, low rigidity and low heat resistance of polypropylene material are solved, the low linear expansion, high rigidity and high heat resistance of the material are achieved, and the compatibility and impact resistance of the material are improved.
Patent Information
- Application Number
- CN202411978402.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polypropylene materials have problems of high linear expansion, low rigidity and low heat resistance, and the horizontal and vertical shrinkage and linear expansion of the material have a large difference, which affects the stability and appearance of the parts.
By introducing high aspect ratio whiskers and fluorogen mica with a larger sheet structure into the polypropylene material, and using a lateral feed and reverse shear module process, the screw shear strength is reduced, ensuring that the structure of the filler is not destroyed, thereby improving the rigidity, heat resistance and shrinkage and linear expansion of the material in the direction of flow.
The low linear expansion, high rigidity and high heat resistance of polypropylene materials are achieved, while reducing the shrinkage and linear expansion differences of the material in the transverse and longitudinal directions, improving the compatibility and impact resistance of the material.
Smart Images

Figure BDA0005220963660000041 
Figure BDA0005220963660000051 
Figure BDA0005220963660000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of modified polypropylene composite materials, and in particular to a low linear expansion, high rigidity and high heat resistance polypropylene composition and a preparation method thereof. Background Art
[0002] Polypropylene has been widely used in automotive parts such as bumpers, dashboards, and fenders due to its low density, low cost, and easy processing. However, compared with many engineering plastics, polypropylene still has many shortcomings, such as large molding shrinkage, high linear expansion coefficient, and poor heat resistance. Therefore, narrowing the differences between polypropylene and engineering plastics in these properties is crucial to further expand the application of polypropylene in the automotive field.
[0003] At present, the main improvement measures for the problems of large shrinkage, large linear expansion coefficient and poor heat resistance of polypropylene materials are to add ultrafine talcum powder, whiskers and long glass fibers and other inorganic substances for extrusion blending modification. However, there are also many problems in these improvement measures that need to be solved urgently. Adding materials with a small aspect ratio, such as ultrafine talcum powder, can greatly improve the rigidity and heat resistance of polypropylene materials, and indeed reduce the linear expansion to a certain extent, but for the automotive industry with increasingly high requirements for dimensional precision, this degree of improvement in linear expansion is insignificant. Adding materials with a large aspect ratio, such as long glass fibers, will significantly improve the linear expansion and shrinkage in the fiber orientation direction, but the differences in longitudinal and lateral shrinkage and linear expansion will be very large, parts will be more prone to problems such as warping and deformation, and the toughness of the material will be significantly reduced.
[0004] Patent document CN 115873338B discloses a low shrinkage polypropylene composite material and a preparation method thereof, wherein expanded perlite is dispersed in ethanol, and then ammonia and other reagents are added to react to finally obtain SiO2-coated expanded perlite. Due to the synergistic effect of the porous void structure of the expanded perlite itself and the voids formed by the surface SiO2, the crystallization behavior of polypropylene is significantly affected, and the formation of large-sized crystals with high crystallinity can be effectively avoided. In addition, steric hindrance will be formed during the crystallization process of the polypropylene material, hindering the shrinkage of the polypropylene material, thereby reducing the shrinkage rate of the material. However, this method has a complicated process, high cost, and limited improvement in the rigidity and linear expansion of the polypropylene material, so it is actually not currently available for large-scale production.
[0005] Patent document CN 201811614238.8 discloses a high-gloss, low-linear expansion coefficient polypropylene composite material and its preparation method. By introducing several whiskers with large aspect ratios (calcium carbonate whiskers, magnesium sulfate whiskers, and basalt whiskers) into the polypropylene blend, the linear expansion coefficient of the material can be effectively reduced. However, this solution does not fully consider the huge differences in transverse and longitudinal shrinkage and linear expansion caused by whiskers, and the parts obtained by injection molding of this material will also be more prone to appearance problems such as warping.
[0006] Patent document CN 117624788A discloses a polypropylene material with low shrinkage and low linear expansion coefficient and a preparation method thereof. The method uses a silane coupling agent as a cross-linking agent and talcum powder and short glass fibers as fillers, which effectively reduces the shrinkage and linear expansion coefficient of the material and relatively avoids the appearance problems such as floating fibers. However, this solution does not fully consider the toughness of the material, and the toughness of the prepared material is relatively low, which also limits the further application prospects of the material.
[0007] Therefore, in order to solve the shortcomings of current polypropylene materials, it is particularly important to prepare and develop a material with low linear expansion, high rigidity and high heat resistance, while taking into account the toughness of the material and fully reducing the differences in material shrinkage and linear expansion in the horizontal and vertical directions. Summary of the invention
[0008] The purpose of the present invention is to break through the bottleneck of the prior art and broaden the application field of polypropylene materials. The present invention provides a low linear expansion, high rigidity and high heat-resistant polypropylene composition and a preparation method thereof, which enhances the rigidity, heat resistance and shrinkage and linear expansion of the material in the flow direction by using a compound of high aspect ratio whiskers and micro-nano-grade mineral powder (10000 mesh). At the same time, in order to reduce the difference in shrinkage and linear expansion of the material in the horizontal and vertical directions caused by the introduction of whiskers, the present invention introduces fluorphlogopite with a larger lamellar structure, which can further enhance the rigidity and heat resistance of the material while effectively reducing the difference in shrinkage and linear expansion in the vertical and horizontal directions of the product. In addition, the present invention feeds the whiskers and fluorphlogopite into the twin-screw extruder in a direct side feeding manner according to a certain proportion, and appropriately reduces the shear strength of the screw, thereby ensuring that the structure of the whiskers and fluorphlogopite is not destroyed to the greatest extent, and effectively increasing its reinforcing effect on polypropylene. In addition, in the patent of the present invention, the twin screw of the extrusion equipment is optimized, and a set of reverse shearing conveying modules are introduced to effectively increase the mixing performance between the components on the material, thereby improving the compatibility between the components and ensuring that the material has good toughness.
[0009] The purpose of the present invention is to provide a method for preparing a modified polypropylene material to solve the shortcomings of high linear expansion, low rigidity and low heat resistance of modified polypropylene. A certain proportion of micro-nano talc powder and whiskers and fluorphlogopite are added to the formula material system, and part of the filler is directly fed into a twin-screw extruder by side feeding according to a certain proportion, and the modified polypropylene material is prepared by blending in the extruder. According to the weight components, it is mainly composed of the following raw materials:
[0010] Polypropylene: 36-73 parts;
[0011] Whiskers: 5.15 parts;
[0012] Mineral powder: 15-25 parts;
[0013] Fluorphlogopite: 0-6 parts;
[0014] Toughener: 5.10 parts;
[0015] Compatibilizer: 1-5 parts;
[0016] Other additives: 1-3 parts.
[0017] The polypropylene copolymer has a melt flow rate of 10 to 80 g / 10 min under the test conditions of 230° C. and 2.16 kg.
[0018] The whiskers are basic magnesium sulfate whiskers with an aspect ratio of 70-100.
[0019] The mineral powder is micro-nano grade mineral powder with a mesh size of 10000 meshes.
[0020] The fluorophlogopite has a melting point of 1375°C, is completely transparent, has a surface roughness of less than 1 nanometer, and a density of 2.78-2.85 g / cm 3
[0021] The toughening agent is POE 7467, with a weight average molecular weight of 50,000 to 80,000.
[0022] The compatibilizer is maleic anhydride grafted polypropylene.
[0023] The other auxiliary agents are antioxidants and light stabilizers. The antioxidants include primary antioxidants and secondary antioxidants, and the primary and secondary antioxidants are a combination of one or more of 1010, 168 and DSTP. The light stabilizer is hindered amine compound 5229.
[0024] Further, in some embodiments of the present invention, a method for preparing a low linear expansion, high rigidity and high heat resistance polypropylene composition, the specific steps are as follows: polypropylene resin, talcum powder, toughening agent, compatibilizer, main and auxiliary antioxidant additives and light stabilizer are mixed evenly and then fed into the main feeding port of a twin-screw extruder, whiskers and fluorphlogopite are fed into the side feeding port of a twin-screw extruder, the temperature of the twin-screw extruder is set to 200-250°C, and a polypropylene composite material is obtained after melt extrusion, cooling, drying and pelletizing. Talc is fed directly into the twin-screw extruder, and whiskers and fluorphlogopite are fed by the side feeding method, which can effectively reduce the damage to the structure of whiskers and fluorphlogopite caused by screw shear during extrusion. In addition, the screws are rearranged and combined to appropriately reduce the shear strength of the screws, thereby ensuring that the structure of whiskers and fluorphlogopite is not destroyed to the greatest extent. At the same time, in order to ensure that various fillers can be fully mixed evenly after the shear strength of the screw is reduced, a reverse shear module is introduced into the screw, which is conducive to improving the compatibility of PP resin, talcum powder, whiskers and fluorophlogopite, thereby further improving the impact resistance of the composite material.
[0025] Polypropylene resin, talcum powder, toughening agent, compatibilizer, main and auxiliary antioxidant additives and light stabilizer enter the twin-screw extruder through the main feeding port, and whiskers and fluorphlogopite are directly fed into the twin-screw extruder through the side feeding port.
[0026] Furthermore, the present invention appropriately reduces the shear strength of the screw and introduces a set of reverse conveying modules to ensure that the polypropylene resin, whiskers and fluorphlogopite in the material can be fully mixed and uniform. The present invention uses 30°, 45°, 60°, and 90° shear block combinations, and at the same time, studies the effects of different shear strengths on material properties. The specific screw combination is shown in the following table:
[0027]
[0028] Note: The larger the angle of the shear module, the stronger the shearing; the larger the angle of the reverse conveying module, the stronger the conveying capacity;
[0029] The compatibility of composite materials and the number of whisker agglomerations (notched impact performance & number of whisker agglomerations on the sample surface) under different combinations are shown in the following table, among which combination 8 is the preferred solution of this patent:
[0030]
[0031] Among them, the specific test methods for notched impact strength and whisker agglomeration quantity are as follows:
[0032] Notched impact strength, tested according to ISO 179-1.
[0033] The number of whisker clusters was determined by injection molding the composite material to obtain a 150*100*3.2 mm sample, and the number of undispersed whisker clusters on the sample was counted.
[0034] Compared with the prior art, the advantages of the present invention are:
[0035] (1) The present invention introduces whiskers with a high aspect ratio and fluorphlogopite with a larger lamellar structure into the polypropylene composite material, so that the composite material has excellent low linear expansion and low shrinkage properties. At the same time, it effectively changes the characteristic of traditional low linear expansion and low shrinkage materials that the difference in lateral and longitudinal linear expansion and shrinkage is too large.
[0036] (2) By adding high aspect ratio whiskers and fluorophlogopite, combined with the reduction of screw shear strength and the side feeding process, the present invention ensures that the structures of whiskers and fluorophlogopite are not destroyed to the greatest extent, and the obtained polypropylene composite material has better heat resistance and rigidity, and excellent mechanical properties.
[0037] (3) The present invention optimizes the processing technology and basic equipment. While ensuring that the whiskers and fluorophlogopite structures are not destroyed to the greatest extent, combined with the improvement of the processing equipment, a reverse shear module is introduced to effectively improve the dispersion effect between the polypropylene material and the filler, thereby further improving the compatibility and impact resistance of the material.
[0038] (4) The present invention has a simple production process and a low formula cost. It has great application prospects in product parts that require high dimensional stability and mechanical properties of material products, especially in the field of automotive parts, such as fenders, all-plastic tailgates, and other parts that use plastics instead of steel. DETAILED DESCRIPTION
[0039] The present invention is further explained below in conjunction with specific embodiments and comparative examples. It should be noted that these embodiments and comparative examples are supplementary explanations of the present invention and should not be construed as limiting the present invention. After reading the contents of the present invention, modifications or changes made to the present invention by those skilled in the art are also within the scope defined by the claims.
[0040] The main materials used in the embodiments and comparative examples are as follows. Polypropylene resin, brand BX3900, melt flow rate 60, manufactured by SK Chemical. Toughener is POE 7467, manufactured by Dow Chemical. Micro-nano grade mineral powder, mesh size 10000 mesh, manufactured by Liaoning Xinda. Basic magnesium sulfate whisker, aspect ratio 70-100, a commercial product. Fluorphlogopite, a commercial product. The compatibilizer is maleic anhydride grafted polypropylene, a commercial product. The main and auxiliary antioxidants are 1010, 168 and DSTP, a commercial product. The light stabilizer is 5229, a commercial product.
[0041] The screw / reverse conveying module combinations 1 to 8 are as shown in the product instructions.
[0042] Example 1
[0043] 57 parts of PP, 3 parts of compatibilizer PP-g-MAH, 25 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 5 parts of whiskers were fed from the side feed port, and the combination of screw / reverse shear modules 5 to 8 were extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0044] Example 2
[0045] 57 parts of PP, 3 parts of compatibilizer PP-g-MAH, 20 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 10 parts of whiskers were fed from the side feed port, and the combination of screw / reverse shear modules 5 to 8 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0046] Example 3
[0047] 57 parts of PP, 3 parts of compatibilizer PP-g-MAH, 15 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 15 parts of whiskers were fed from the side feed port, and the combination of screw / reverse shear modules 5 to 8 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0048] Example 4
[0049] 55 parts of PP, 3 parts of compatibilizer PP-g-MAH, 15 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 15 parts of whiskers and 2 parts of fluorphlogopite were fed from the side feed port, and the combination of screw / reverse shear modules 5 to 8 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0050] Example 5
[0051] 53 parts of PP, 3 parts of compatibilizer PP-g-MAH, 15 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 15 parts of whiskers and 4 parts of fluorphlogopite were fed from the side feed port, and the combination of screw / reverse shear modules 5 to 8 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0052] Example 6
[0053] 51 parts of PP, 3 parts of compatibilizer PP-g-MAH, 15 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feeding port of the twin-screw extruder, 15 parts of whiskers and 6 parts of fluorphlogopite were fed from the side feeding port, and the combination of screw / reverse shear modules 5 to 8 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0054] Comparative Example 1
[0055] 57 parts of PP, 3 parts of compatibilizer PP-g-MAH, 25 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 5 parts of whiskers were fed from the side feed port, and the combination of screw / reverse shear modules 1 to 4 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0056] Comparative Example 2
[0057] 57 parts of PP, 3 parts of compatibilizer PP-g-MAH, 20 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 10 parts of whiskers were fed from the side feed port, and the combination of screw / reverse shear modules 1 to 4 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0058] Comparative Example 3
[0059] 57 parts of PP, 3 parts of compatibilizer PP-g-MAH, 15 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 15 parts of whiskers were fed from the side feed port, and the combination of screw / reverse shear modules 1 to 4 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0060] Comparative Example 4
[0061] 55 parts of PP, 3 parts of compatibilizer PP-g-MAH, 15 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 15 parts of whiskers and 2 parts of fluorphlogopite were fed from the side feed port, and the combination of screw / reverse shear modules 1 to 4 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0062] Comparative Example 5
[0063] 53 parts of PP, 3 parts of compatibilizer PP-g-MAH, 15 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 15 parts of whiskers and 4 parts of fluorphlogopite were fed from the side feed port, and the combination of screw / reverse shear modules 1 to 4 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0064] Comparative Example 6
[0065] 51 parts of PP, 3 parts of compatibilizer PP-g-MAH, 15 parts of 10000 mesh mineral powder, 8 parts of toughening agent and 2 parts of other additives were fully mixed and then added from the main feed port of the twin-screw extruder, 15 parts of whiskers and 6 parts of fluorphlogopite were fed from the side feed port, and the combination of screw / reverse shear modules 1 to 4 was extruded for granulation. Among them, the extrusion melt blending temperature was 230°C, and the vacuum was turned on during extrusion and the vacuum degree was maintained at -0.08MPa. After the particles were dried, they were injection molded to make test specimens.
[0066] The formulations and screw / reverse shear module combinations of the embodiments and comparative examples are shown in Table 1 below.
[0067] Table 1 Material formula of Examples 1-6 and Comparative Examples 1-6 and their screw / reverse shear module combinations
[0068]
[0069]
[0070] Performance Testing
[0071] The bending modulus of the material was tested according to ISO 178 method, with a speed of 2mm / min and a span of 64mm; the heat deformation temperature was tested according to ISO 75-2 method, with a load of 0.45MPa. The notched impact strength was tested according to ISO 179.1 method. The Flow linear expansion and Cross Flow linear expansion were tested according to ISO 11359-2 method, with a temperature range of -30-80℃. The number of whisker agglomerates was calculated by injection molding the composite material into a 150*100*3.2mm sample, and the number of undispersed whisker clusters on the sample was counted.
[0072] Table 2 Relevant properties of materials prepared in Example 1.6 and Comparative Examples 1-6
[0073]
[0074]
[0075] Table 2 shows the relevant properties of the materials prepared in Example 1.6 and Comparative Example 1.6. After comparing the properties, the following conclusions can be drawn:
[0076] 1. By comparing Examples 1-6 and Comparative Examples 1-6, it can be found that after the reverse shear module is introduced into the process equipment, the number of whisker agglomerates is significantly reduced as a whole, the compatibility of the composite material is improved, and the notched impact performance of the overall material is significantly improved.
[0077] 2. From the comparison of Examples 1-3, it can be found that high aspect ratio whiskers have a significant effect on strengthening the mineral powder system. Under the condition of the same overall filler content, the addition of high aspect ratio whiskers can significantly improve the rigidity and heat resistance of the material, and at the same time, greatly reduce the linear expansion of the composite material. From the comparison of Example 3.6, it can be found that after the introduction of fluorophlogopite with a larger sheet structure, the rigidity and heat resistance of the composite material are further improved, and the linear expansion is further reduced. At the same time, the addition of fluorophlogopite has significantly reduced the linear expansion difference of the composite material in the longitudinal and transverse directions. The polypropylene composite material prepared by the present invention has high heat resistance and rigidity, and excellent mechanical properties. And improves the compatibility and impact resistance of the material. The present invention has a simple production process and a low formula cost. It has great application prospects in product parts that require high dimensional stability and mechanical properties of material products, especially in the field of automotive parts, where plastic replaces steel parts such as fenders, all-plastic tailgates and other parts.
[0078] Finally, it should be emphasized that the present invention provides an efficient solution for low linear expansion, high rigidity and high heat resistance polypropylene composite materials, which is not limited to the whiskers and fluorphlogopite used in the present invention, but can also be applied to other similar systems. After reading the contents of the present invention, those skilled in the art can make modifications or changes to the present invention, and these changes also fall within the scope defined by the claims.
Claims
1. A low linear expansion, high rigidity and high heat resistance polypropylene composition, characterized in that: The following raw materials are prepared according to weight ratio composition: Polypropylene: 36-73 parts; Whiskers: 5.15 parts; Mineral powder: 15-25 parts; Fluorphlogopite: 0-6 parts; Toughener: 5.10 parts; Compatibilizer: 1.5 parts; Other additives: 1.3 parts.
2. A low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 1, characterized in that: The polypropylene resin is conventional copolymerized polypropylene, and under the test conditions of 230° C. and 2.16 kg, the melt flow rate of the polypropylene is 10 to 80 g / 10 min.
3. The low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 1, characterized in that: The whiskers are basic magnesium sulfate whiskers with a high aspect ratio of 70.
100.
4. The low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 1, characterized in that: The mineral powder is micro-nano grade mineral powder with a mesh size of 10000 meshes.
5. The low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 1, characterized in that: The fluorphlogopite has a melting point of 1375°C and a density of 2.78-2.85 g / cm 3 .
6. The low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 1, characterized in that: The toughening agent is POE 7467, with a weight average molecular weight of 50,000 to 80,000.
7. The low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene.
8. The low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 1, characterized in that: The other auxiliary agents are antioxidants and light stabilizers. The antioxidants include primary antioxidants and secondary antioxidants, and the primary and secondary antioxidants are a combination of one or more of 1010, 168 and DSTP; the light stabilizer is hindered amine compound 5229.
9. The method for preparing the low linear expansion, high rigidity and high heat resistance polypropylene composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: uniformly mixing polypropylene resin, talcum powder, toughening agent, compatibilizer, main and auxiliary antioxidant additives and light stabilizer and then feeding the mixture into a main feeding port of a twin-screw extruder; feeding whiskers and fluorphlogopite into a side feeding port of the twin-screw extruder; setting the temperature of the twin-screw extruder to 200-250°C; and obtaining a polypropylene composite material after melt extrusion, cooling, drying and pelletizing.
10. The method for preparing the low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 9, characterized in that: Polypropylene resin, talcum powder, toughening agent, compatibilizer, main and auxiliary antioxidant additives and light stabilizer enter the twin-screw extruder through the main feeding port, and whiskers and fluorphlogopite are directly fed into the twin-screw extruder through the side feeding port.
11. The method for preparing the low linear expansion, high rigidity and high heat resistance polypropylene composition according to claim 9, characterized in that: A set of reverse conveying modules was introduced to ensure that the polypropylene resin, whiskers and fluorphlogopite in the material could be fully and evenly mixed; a combination of 30°, 45°, 60° and 90° shear blocks were used respectively.
Citation Information
Patent Citations
Polypropylene composite material with high gloss and low linear expansion coefficient and preparation method thereof
CN109721839A
A low shrinkage polypropylene composite material and preparation method thereof
CN115873338B
Polypropylene material with low shrinkage rate and low linear expansion coefficient and preparation method thereof
CN117624788A
Isotropic polypropylene composition with low linear expansion coefficient and preparation method thereof
CN103665544A
Polypropylene composite material with low linear expansion coefficient and preparation method and application thereof
CN106147034A